2019
DOI: 10.1111/jai.13857
|View full text |Cite
|
Sign up to set email alerts
|

Ions and osmolality on post‐thaw sperm motility activation of the endangered Brycon insignis (Characiformes)

Abstract: Summary The aim of this study was to evaluate the effects of osmolality and the presence of ions on the activation of post‐thaw sperm motility of Brycon insignis. Sperm was frozen under a standardized methodology for this species. In experiment 1, 11 solutions were prepared with reverse osmosis (RO) water (∼0 mOsm/kg) and glucose or NaCl adjusted to an osmolality of 50, 100, 150, 200 and 250 mOsm/kg. In experiment 2, six solutions were prepared with RO and adjusted to ~100 mOsm/kg with one of the following che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…These results agree with Aramli & Nazari (2014), who reported a 47 % decrease in the sperm motility of the Persian sturgeon Acipenser persicus 60 min after thawing. Viveiros et al (2019) observed a significant reduction in the activation capacity of Brycon insignis sperm after 20-25 min post-thaw. They have also observed it in the salmon river Brycon orbignyanus Valenciennes and dorado Salminus brasiliensis Cuvier, just a few seconds after thawing.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…These results agree with Aramli & Nazari (2014), who reported a 47 % decrease in the sperm motility of the Persian sturgeon Acipenser persicus 60 min after thawing. Viveiros et al (2019) observed a significant reduction in the activation capacity of Brycon insignis sperm after 20-25 min post-thaw. They have also observed it in the salmon river Brycon orbignyanus Valenciennes and dorado Salminus brasiliensis Cuvier, just a few seconds after thawing.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, in the silver barb Barbodes gonionotus, sperm motility was significantly reduced in thawed semen 10 months after cryo-storage (Vuthiphandchai et al, 2015). Viveiros et al (2019) evaluated B. insignis semen cryopreserved for five years, reporting post-thaw motility above 70 % through the use of different activator solutions with a wide range of osmolalities (0-200 mOsm kg -1 ), including SB and SC, without finding significant differences in the post-thaw motility obtained by the use of these two substances.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The positive correlation of Ca 2+ concentration in seminal plasma with ROS levels, and the negative correlation between this ion and post‐thaw sperm motility rate indicate that the interaction of these agents disturbed spermatozoa metabolism. The negative effects of Ca 2+ on sperm motility have been demonstrated in characiforms and cyprinids (França et al, 2020; Khara et al, 2014; Viveiros et al, 2019). The freezing and thawing process disturb the mitochondrial oxidative metabolism, leading to enhanced ROS generation and dysregulation of mitochondrial Ca 2+ homeostasis, which in turn stimulates an increase in mitochondrial oxidative metabolism, resulting in mitochondrial dysfunction, impairment of ATP synthesis (Brookes et al, 2004) and ultimately loss of post‐thaw sperm motility (Figueroa et al, 2016, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NaCl solution at a concentration of 325 mOsm kg -1 and a pH of 7.6 guarantees the immobility of sperm by promoting conditions similar to seminal plasma. In addition, the presence of NaCl at the time of activation potentiates the sperm kinetic parameters (Viveiros et al, 2019), increasing the chances of fertilization.…”
Section: Introductionmentioning
confidence: 99%